2019
DOI: 10.1016/j.eclinm.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk of a second cancer in Canadians diagnosed with a first cancer in childhood or adolescence

Abstract: BackgroundSecond cancers are an adverse outcome experienced by childhood cancer survivors. We quantify the risk and correlates of a second cancer in Canadians diagnosed with a first cancer prior to age 20 years.MethodsUsing death-linked Canadian Cancer Registry data, a population-based cohort diagnosed with a first cancer between 1992 and 2014, prior to age 20 years, were followed for occurrence of a second cancer to the end of 2014. We estimate standardized incidence ratios (SIR), absolute excess risks (AER),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies investigating the development of any kind of SMN among a mixed-cancer population and reporting a single overall estimate for the standardized incidence ratio (SIR) found that AYA cancer survivors were 1.6 (95% confidence interval [95% CI]:1.6–1.6) to 4.3 (95% CI:3.6–5.1) times more likely to experience an SMN relative to that of a primary malignant neoplasm expected in the general population ( Table 1 ) [ 17 , 18 , 19 , 20 ]. Absolute excess risk (AER) for developing an SMN in these same cohorts ranged between 15.9 (95% CI:12.1–19.8) and 25.9 (95% CI not reported) per 10,000 person-years at risk.…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigating the development of any kind of SMN among a mixed-cancer population and reporting a single overall estimate for the standardized incidence ratio (SIR) found that AYA cancer survivors were 1.6 (95% confidence interval [95% CI]:1.6–1.6) to 4.3 (95% CI:3.6–5.1) times more likely to experience an SMN relative to that of a primary malignant neoplasm expected in the general population ( Table 1 ) [ 17 , 18 , 19 , 20 ]. Absolute excess risk (AER) for developing an SMN in these same cohorts ranged between 15.9 (95% CI:12.1–19.8) and 25.9 (95% CI not reported) per 10,000 person-years at risk.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence and risk factors for SMNs have been introduced by many researchers. Zakaria et al ( 20 ) found that, among 22,635 people surviving childhood cancer, 395 patients had a secondary malignancy with an additional nearly fivefold risk than expected in the general population. The most common site was the thyroid, followed by the breast and oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Since comprehensive examination at the first diagnosis can artificially inflate the risk of SMN in the first 60 days following a diagnosis, cancer diagnoses within 60 days of the first diagnosis were considered part of the initial diagnosis. This 60-day window has been used in other studies to decrease the risk of differential surveillance ( 16 , 21 , 22 ) into one of the seven main diagnostic types of childhood cancer ( Table 1 ) to mitigate small numbers of events. Only the first SMN was used to indicate a SMN as there were very few cases with multiple SMNs.…”
Section: Methodsmentioning
confidence: 99%